Korea's economy : - Woronoff, Jon (Si-sa-yong-o-sa Publishers, 1983)
Contents: What galvanized the population and how the economy was constructed form the contens of this book. It includes an overview of plans and strategies, policies and implementation, and a look at some of the crucial sectors